2020
DOI: 10.1111/mve.12499
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of insects to African swine fever virus dispersal: data from domestic pig farms in Lithuania

Abstract: Outbreaks of African Swine Fever (ASF) in domestic pig farms in Lithuania typically begin in June and are detected through October, suggesting that insects might be involved in the transmission of the virus. Entomological collecting was performed to obtain two data sets: from farms with ASF outbreaks, and from farms without ASF outbreaks but in an ASF‐infected area. Target insects from the families Muscidae, Calliphoridae and Tabanidae were analysed for the presence of ASF Virus (ASFV) DNA. Musca domestica L.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…This is also in agreement with a study from Estonia, where various groups of blood-feeding arthropods were collected in ASFV-affected wild boar habitats but tested negative for the presence of the ASFV genome [ 144 ]. However, mechanical transmission on a laboratory scale was reported with the stable fly (Stomoxys calcitrans ) [ 145 ] and two studies from Eastern Europe have reported the detection of a low amount of ASFV genome on insects collected on domestic pig outbreak sites [ 146 , 147 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…This is also in agreement with a study from Estonia, where various groups of blood-feeding arthropods were collected in ASFV-affected wild boar habitats but tested negative for the presence of the ASFV genome [ 144 ]. However, mechanical transmission on a laboratory scale was reported with the stable fly (Stomoxys calcitrans ) [ 145 ] and two studies from Eastern Europe have reported the detection of a low amount of ASFV genome on insects collected on domestic pig outbreak sites [ 146 , 147 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The second reason may be that with applied biosecurity measures not all transmission routes are controlled. Due to the strong seasonal pattern in the occurrence of ASF outbreaks in domestic pigs (the summer season) the role of blood-sucking insects in virus transmission has been discussed [ 30 , 31 , 32 ]. In Estonia, pig stables are not insect-proof and this has not been considered as necessary to date.…”
Section: Discussionmentioning
confidence: 99%
“…M. domestica has also been reported to mechanically transmit several types of viral pathogens to livestock including: avian influenza virus (AIV), both high and low pathogenic strains [46,[212][213][214][215][216], turkey coronavirus (TCV) [217], Newcastle disease virus (NDV) [218][219][220][221][222], reticuloendotheliosis virus (REV) [223], porcine reproductive and respiratory syndrome virus (PRRSV) [224][225][226][227][228], porcine circovirus genotype 2 (PCV2b) [229], porcine epidemic diarrhea virus (PEDV) [230], African swine fever virus (ASF) [231,232], Aujeszky's virus (PRV-1) [233], senecavirus A (SVA) [234], Rift Valley fever virus (RVFV) [235], Aleutian mink disease virus (AMDV) [236,237], and lumpy skin disease (LSDV) [238,239].Viruses detected in dipteran edible species are listed in Table 4. The lesser wax moth, Achroia grisella, is a species closely related to Galleria mellonella [241].…”
Section: Musca Domesticamentioning
confidence: 99%